Introducción al estudio del poblamiento beréber en la marca superior de al-Andalus (siglos viii-xii) - Bilal Sarr (Mélanges de la Casa de Velázquez)
This article offers a preliminary outline of the findings emerging from the research programme on Berber settlement in the Upper March of al-Andalus (8th-12th centuries). It also reports on the status of the research into this subject and finally proposes a number of lines for future research. We should note that the data yielded by written sources and toponymics have already furnished more information than had been expected.